Performance Comparison of Routing Protocols for Underwater Sensor Networks - Memon, Komal; Bohra, Nafeesa; K Shaikh, Faisal (International Journal of Engineering and Technology, 2018)
There is a great demand of an Underwater Sensor Networks (UWSNs) in applications of water monitoring and offshore exploration. In such applications, network comprises of multiple sensor nodes which are deployed at different locations and depths of water. Sensor nodes perform collective tasks such as data collection and data transmission to other nodes or Base Station (BS). The bottom nodes are located at depth of water, and are not able to communicate directly with the surface level nodes, these nodes require multi-hop communication with appropriate routing protocol. Therefore, an energy efficient routing protocols are used for such scenarios, which is necessary as well as challenging task. As sensors are battery operated devices, which are really problematic to recharge or replace. The error and propagation path delays are high in acoustic channels therefore underwater communication is much effected. Realizing the circumstances, more attention has been given to compare energy efficient routing protocols which comparatively consume low energy and achieve high throughput. This paper, comprises of analysis and comparison of existing UWSN based efficient energy routing protocols. Based upon the analysis and comparison, VBF and DBR have been proposed that fulfill the requirements. The analysis is done on NS-2 and for comparison, the performance metrics which are evaluated are: Packet delivery Ratio (PDR), energy consumption, throughput and average End to End (E2E) delay. The results show that VBF protocol consume very large amount of energy as compared to DBR protocol. Whereas DBR protocol have characteristics like low energy consumption, minimum delay high PDR and high throughput than VBF protocol.Â Â